2019
DOI: 10.1016/j.euf.2019.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Features of Metastatic Testicular Sex Cord Stromal Tumors

Abstract: Background: Metastatic testicular sex cord stromal tumors of the testis (MSCSTs) comprise an extremely uncommon form of genitourinary malignancy. Objective: To perform comprehensive genomic profiling (CGP) to enable the search for potential therapy targets. Design, setting, and participants: Ten patients with testicular Leydig cell tumors (LCTs), six with Sertoli cell tumors (SCTs), and three with undifferentiated sex cord stromal tumors (USCSTs) and a comparison group of 366 patients with ovarian sex cord str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 30 publications
(54 reference statements)
1
26
0
Order By: Relevance
“…Imatinib, a selective tyrosine kinase inhibitor, has been shown to decrease viability of Leydig tumor cell lines [19]. Furthermore, with the advent of the use of genomics and precision medicine, future therapeutic regimens could potentially be tailored for these patients and may help improve treatment outcomes in patients with advanced disease [20]. Necchi et al performed comprehensive genome profiling on the tumors of 10 patients with metastatic SCSTs and reported that, although uncommon, several tumors expressed targetable genomic alterations indicating the potential efficacy of cell-cycle, mTOR, hedgehog, and polymerase inhibitors [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imatinib, a selective tyrosine kinase inhibitor, has been shown to decrease viability of Leydig tumor cell lines [19]. Furthermore, with the advent of the use of genomics and precision medicine, future therapeutic regimens could potentially be tailored for these patients and may help improve treatment outcomes in patients with advanced disease [20]. Necchi et al performed comprehensive genome profiling on the tumors of 10 patients with metastatic SCSTs and reported that, although uncommon, several tumors expressed targetable genomic alterations indicating the potential efficacy of cell-cycle, mTOR, hedgehog, and polymerase inhibitors [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, with the advent of the use of genomics and precision medicine, future therapeutic regimens could potentially be tailored for these patients and may help improve treatment outcomes in patients with advanced disease [20]. Necchi et al performed comprehensive genome profiling on the tumors of 10 patients with metastatic SCSTs and reported that, although uncommon, several tumors expressed targetable genomic alterations indicating the potential efficacy of cell-cycle, mTOR, hedgehog, and polymerase inhibitors [20]. A case-series by Calaway et al reported that two patients with disseminated SCSTs had tumor genetic susceptibility testing following retroperitoneal lymph This study is not without limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited life expectancy of patients with metastastic disease, as well as limited experience with systemic cancer therapies versus germ-cell cancer therapies, experimental targeted approaches or immunotherapy could be considered. However, exploratory findings show only limited, targetable genomic alterations and low tumor mutational burden, arguing against checkpoint inhibition [23].…”
Section: Discussionmentioning
confidence: 99%
“…Necchi et al explored the genomic changes in malignant TSCSTs and found that the microsatellite instability mutation rate is low and that it has the characteristics of a low TMB. Thus, they speculated that the response to immunotherapy would be limited (22). However, Aguilar et al found that the growth rate of TSCSTs in mice could be significantly decreased by injecting an inhibin-a vaccine in advance.…”
Section: Discussionmentioning
confidence: 99%
“…explored the genomic changes in malignant TSCSTs and found that the microsatellite instability mutation rate is low and that it has the characteristics of a low TMB. Thus, they speculated that the response to immunotherapy would be limited ( 22 ). However, Aguilar et al.…”
Section: Discussionmentioning
confidence: 99%